An iPhone app of Konza Prairie LTER - Nukala, Leela Anusha (Kansas State University, 2012)
The objective of this project is to develop an iPhone application for the Konza Prairie LTER and play a significant role in the development of their website. The data of the Konza Prairie LTER is vast and includes the spatial datasets, weather reports, text archives, information about the flora and fauna at Konza Prairie Natural Area, integrated project areas, Dataset Codes, LTER Core Areas, Related projects, Konza Documents and Permits, and Publications. The module which was developed by me provides users information like publications, personnel information and datasets. The titles of the publications along with their PIs will be retrieved from the database and formatted onto the webpage. The 'Personnel' page has links directing to Primary Contacts, Faculty and Staff and Graduate Students. The attractive feature of this personnel page is that each personnel in the list will have a '+' link which enables the user more information about that particular personnel like their field of interests, mailing address and a link to view their profile. As the website already has all the required data and information in detail, the mobile app only briefs about them. People who are working on-site can make of this app efficiently as its features includes list of upcoming events, map of Konza with GPS feature, Post Card feature, Primary personnel to be contacted and other features. The website is developed using Visual Studio 2010 and SQL Server 2008 database. The iPhone app enhanced my knowledge and provided me with real-time exposure to iPhone SDK tools, X-code, Interface builder and its development environment.
Keywords: iPhone; Konza; Computer Science (0984)